DIGITAL AND DIALOGIC PEDAGOGIES IN BRAZIL’S ELEMENTARY CLASSROOMS: TOWARD TRANSFORMATIVE LEARNING - Dennison J., Evans (CV. Fahr Publishing, 2024)
This study aims to identify and analyze innovative strategies to bridge learning gaps in literacy and numeracy among primary school students in rural Ghana. The focus is on instructional practices that integrate level-based teaching, contextual learning materials, and the active involvement of community and low-tech digital tools. A descriptive qualitative approach was employed, involving two primary schools located in Techiman North and Ahafo Ano South East Districts. A total of 52 participants—including teachers, students, and community facilitators—were engaged. Data were collected through classroom observations, semi-structured interviews, and analysis of student learning documents, and were thematically analyzed. The findings indicate that grouping students by proficiency in numeracy and literacy led to an average improvement of 26% in numeracy scores among lower-level students over six weeks. The use of culturally relevant reading materials and folklore enhanced reading motivation and improved students' narrative writing skills. In addition, mobile library programs and local audio-book activities increased the frequency and quality of student reading engagement. The novelty of this study lies in its integration of contextual pedagogy with low-tech interventions such as a WhatsApp-based AI tutor. This hybrid model shows strong potential for replication in other low-resource settings globally, offering a scalable and sustainable approach to improving foundational learning equity.